PERBANDINGAN POLA PENAMAAN MAHASISWA BERDASARKAN LATAR BELAKANG AGAMA, MAKNA, DAN KANDUNGAN PENDIDIKAN KARAKTER - Priska Meilasari; Agnes Adhani (Universitas Muhammadiyah Kotabumi, 2023)
This research aims at (1) analyzing the comparison of Islam and Catholic Students’ names naming pattern based on word class combination and nomenclature pattern, (2) analyzing the comparison of religious background (Islam and Catholic) influence towards Students’ names, (3) analyzing the comparison of Islam and Catholic Students’ names meaning by referring to the references, and (4) analyzing the character building value carried by the names based on the six Pancasila Student Profiles as a reflection of Nation value-based character building. The data of the research are the names of 75 students of State Institute of Islam Religion (IAIN) Ponorogo and 75 students of Education and Teacher Training Institute (STKIP) Widya Yuwana Madiun. The research result shows that based on the word count, most Catholic and Islam names are made of three words with the combination of Adj+N+N for Islam names and N+N+N for Catholic names. Based on the influence of religious background, 35 Islam name reflect Arab language and 52 Catholic names reflect European and Indonesian language. Based on the meaning carried by each names, both Islam and Catholic names convey hope, prayer, and gender marking meanings. Finally, character building values reflected from the names are (1) having faith and fearing God Almighty, and having noble character, (2) global chitizenship, (3) creative.